Effectiveness of Kinaesthetic Exercise program on Position Sense, Pain, and Disability in Chronic Neck Pain Patients with Cervical Spondylosis – A Randomized Comparative Trial - Reddy, Ravi Shankar Yerragonda; Maiya, Arun G; Rao, Sharath Kumar; Alahmari, Khalid A; Tedla, Jaya Shanker; Kandakurti, Praveen Kumar; Kakaraparthi, Venkata Nagaraj (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2020)
Background Chronic neck pain (CNP) is a significant health problem with only a few evidence-based treatment options. There is growing evidence for the effectiveness of kinaesthetic rehabilitation in musculoskeletal disorders. This study aims to assess kinaesthetic exercise programs' efficacy on cervical position sense, pain, and disability in subjects with cervical spondylosis (CS).Methods CNP subjects (>3 months) with a diagnosis of CS were randomly assigned to either a study group (n=125) who received kinesthetic exercises or to a comparative group (n=125) who received isometric neck exercises and deep cervical flexor (DCF) strengthening exercises. Both group subjects participated in the individualized training program for 24 sessions in 6 weeks. The outcome measures were cervical joint position errors (JPE’s) in flexion, extension, rotation left and right, pain intensity, and neck disability.Results All outcomes were improved significantly from baseline to post 24 sessions of intervention. When compared between groups, there was a significant reduction in JPE’s in flexion (mean difference [MD]= 071, CI=0.22–1.20, p=0.001), extension (MD=1.26, CI=0.70–1.81, p< 0.001) and right rotation (MD=1.08, CI=0.58–1.58, p<0.001), pain intensity (MD=1.58, CI=1.09–2.08, p<0.001), and neck disability (MD=10.27, CI=7.42–13.12, p<0.001) after 24 sessions of intervention favoring the study group.Conclusion Study group subjects who received kinesthetic rehabilitation showed more significant improvements in terms of improved proprioception, decreased pain intensity and disability following 24 sessions of interventions compared with the comparative group.
Keywords: Cervical spondylosis; neck pain; proprioception; kinesthesia; head reposition sense